BIOCOMPATIBILIDAD DEL IONÓMERO DE VIDRIO FLUORADO EN CAVIDADES PROFUNDAS CLASE I - Velezmoro L., Víctor (2000)
The present research concening the biocompatibility of fluoridated glass iotioniers on the dentin surface was developed, using sample of 30 extracted teeth with lesions on occlusal surfaces and without extension into the inteproximal surfaces. This condition was verified in pediatric patients receiving care in the UNMSM Dental clinic. During the period of the research all three cements studied resulted in similar clinical performance with no reports of pain in any of the treatment cases, being similar the clinical behavior of the three studied cements. With respect to the marginal seal, our appraisal determined that the FUJI IX cement offered the best seal of the dentinal wall and that the IONOMOLAR cement resulted in the greatest leakage at this level. The observations taken during the bacteriologic phase showed a reduction in the level of streptococcus mutans in 70% of the samples studied. Varied results were seen in the relative observations of the hermetic seal of the cements; FUJI IX showing the least amount of leakage in comparation with IONOMOLAR.